EVALUASI PEMEKARAN DAERAH DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT - Ropiko Duri; Mutia Rahmah (Fakultas Politik Pemerintahan IPDN, 2020)
Evaluation of regional expansion of Empat Lawang regency is expected to focus more on the results of policies that have been carried out after regional expansion and analyze how far the success rate of efforts to realize welfare for the community during the 10 years after the regional expansion. The welfare in this case is a condition that shows a better state than the condition before the policy. This research uses descriptive qualitative research design, data collection techniques through interviews, observations, and documentation. The selection of informants is based on purposive sampling techniques and snowball sampling. The study used three main indicators in looking at welfare development consisting of education, health services, and the development of people's income levels. The study used evaluation criteria from William N Dunn. The results showed that the Policy of regional expansion of Empat Lawang Regency has not been able to fully improve the welfare of the community and still shows a slow development trend, as seen from: 1) the effectiveness criteria are large numbers. the number of people dropping out of school, limited health personnel, and a decline in economic growth last year and a decline in GRDP in the past year; 2) the criteria for adequacy have not been able to show the level of effectiveness in meeting community needs; 3) equal distribution criteria in the form of uneven access to education; 4) responsiveness criteria in the form of a lack of government response in repairing roads for population mobility; 5) accuracy criteria in the form of inaccurate revocation of the status of disadvantaged areas of Empat Lawang Regency.Keywords: policy, welfare, regional expansion